How do I compose? (Reflections on Wagner Dream) - Harvey, Jonathan (Circuit, 2008)
AbstractWritten in May of 2007, in this text Jonathan Harvey reflects on his compositional method by returning to the genesis of his opera Wagner Dream. He notably addresses such things as: the personal associations connected to the first note played by the horn; the conceptual logic behind the two main harmonic spaces; the effect of a heavy storm in one of the places he composed; and what he drew from Wagner’s work and ideas for his own opera.